Organic Farming: An International History 2007
DOI: 10.1079/9780851998336.0001
|View full text |Cite
|
Sign up to set email alerts
|

What explains the rise of organic farming?

Abstract: An increase in organic farming is thought to be attributed to the subsidization of organic farming (at least for western Europe). However, subsidies, while stimulating convertion to organic farming since the 1990s, were a result, not a cause, of the earlier growing interest in organics in the 1970s and 1980s. In the absence of thorough analysis several possibilities suggest themselves: organic activists were successful in promoting their views to the public, scientists and policy makers; as new concerns emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 0 publications
0
36
0
1
Order By: Relevance
“…They also blamed such "pseudoscientists" for causing panic among the public with regard to paying more for food [19] and also mentioned that the "organic myth" was counterproductive to human welfare, because it leads to a rejection of procedures that are needed for the production of nutritious food at "maximum efficiency" and was "eroding gains of decades of farming advancements". However, 7 years later, the journal of this same AAAS published a major research paper that found organic farms to be highly efficient and economically competitive when compared to conventional farming [7].…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…They also blamed such "pseudoscientists" for causing panic among the public with regard to paying more for food [19] and also mentioned that the "organic myth" was counterproductive to human welfare, because it leads to a rejection of procedures that are needed for the production of nutritious food at "maximum efficiency" and was "eroding gains of decades of farming advancements". However, 7 years later, the journal of this same AAAS published a major research paper that found organic farms to be highly efficient and economically competitive when compared to conventional farming [7].…”
Section: Historymentioning
confidence: 99%
“…scientific and political arenas [2,3], as well as by consumers as a whole. Today, organic farming is a legitimate system due to its history and evolution of practices, and rules and regulations [4,5,6,7].…”
mentioning
confidence: 99%
“…Lockeretz (2007) states that in the absence of fundamental analysis one can only speculate, highlighting several possible answers: -Activists of organic movements were sufficiently successful in promoting their vision to public, researchers and creators of the macroeconomic environment;…”
Section: Introductionmentioning
confidence: 99%
“…When and where in human history does this vague idea of organic agriculture first come to mind? In practice, and in theory (Lockeretz, 2007), one often comes to an opinion that it began centuries ago, when first hunter-gatherers finished with a nomadic lifestyle and began establishing communities and practicing agriculture. However, producers in the distant past certainly did not have at their disposal modern means of chemization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation